Evaluation of Results of Open Reduction and Internal Fixation of Intraarticular Fracture of Distal Humerus AO type 13-C1 by 90-90 Plate Through Triceps Sparing Approach - Hossain Khan, Mohammad Reza; Shameem, Md; Sharmin, Asma; Jahan, Jesmin; Shakhawat Hossain, Syed Mohammad; Harun, Muhammad Eusuf (TAJ: Journal of Teachers Association, 2022)
Background & objective: The complex anatomy of the distal end of the humerus with its unique orientation of articular surfaces supported by cancellous bone makes its fracture a constant challenge to orthopaedic surgeons. Internal fixation techniques seek to stabilize these fractures by using a plate on both columns. Without this dual plate arrangement, stability of fixation can be inadequate. Materials & Methods: This observational, descriptive, longitudinal, prospective study was carried out in the outpatient and inpatient at Department of National Institute of Traumatology and Orthopaedic Rehabilitation (NITOR), Dhaka over a period of two years, between July 2014 to June 2016. Participants were 18 in number and aged between 18 to 50 years. Fractures are classified according to AO classification system and only closed intra-articular fractures of distal humerus AO type 13-C1 was included in this study. Patients with open fractures, fracture more than 2 weeks old and fractures in children were excluded from this study. Majority of cases 11(61.11%) were operated within 1 week of injury. Open reduction internal fixation by pre-contoured 90-90 locking plate was performed in all cases through triceps sparing approach. The plaster cast was removed 2 weeks after operation and rehabilitation was encouraged during this period and afterwards. Patients were advised to come for follow up after discharge in different scheduled date till the fracture union was achieved. The final outcome of the patient was graded according to Mayo Elbow Performance Index (MEPI). Chi-square test was used for testing statistical significance. Statistical significance was set at p < 0.05. Results: Most of the injury was caused by motor vehicle accident 9(50.00%) and rest of the injury caused by fall 5(27.77%). Final outcome by MEPI showed that 15(83.33%) were excellent, 2(11.11%) were good, 1(05.56%) was fair, there was no poor Result. Complications were seen during the follow up period that included wound scar, delayed union which was treated conservatively and union occurred at 18th week. Conclusion: Open reduction and internal fixation of closed intra-articular fractures of distal humerus AO type 13-C1 by 90-90 plate in sagittal plane on medial column and in coronal plane on lateral column through triceps sparing approach is an effective procedure to provide sufficient stability for the postoperative rehabilitation with an excellent union rate and a very good clinical outcome. TAJ 2021; 34: No-2: 71-79